CYTOTOXICITY OF Cynara scolymus (ARTICHOKE), Myracrodruom urundeuva (AROEIRA-DO-SERTAO) AND Camellia sinensis (GREEN TEA) GLYCOLIC EXTRACTS - Higa, Karen Cristiane; Jorjao, Adeline Lacerda; Oliveira, Felipe Eduardo; Oliveira, Jonatas Rafael de [UNESP]; Back Brito, Graziella Nuernberg [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Oliveira, Luciane Dias de [UNESP] (Univ Vale Paraiba-univap, 2019)
Natural products such as glycolic extracts of plants are important for the clinical application in health care, like mouthwashes, toothpastes and intracanal irrigation. It is therefore necessary to perform cytotoxicity studies of these glycolic extracts. Objectives: This study aimed to assess the cytotoxic activity of Cynara scolymus (artichoke), Myracrodruom urundeuva Allem. (aroeira-do-sertao) and Camellia sinensis (L.) Kuntze (green tea) glycolic extracts in mouse macrophages (RAW 264.7) by the MTT metabolic activity test. Design: Macrophages were distributed into 96-well plates and exposed to 11 serial dilutions of each extract (200 mg/mL, 100 mg/mL, 50 mg/mL, 25 mg/mL, 12.5 mg/mL 6.25 mg/mL, 3.13 mg/mL, 1.56 mg/mL, 0.78 mg/mL, 0.39 mg/mL and 0.20 mg/mL), with n=8 for each dilution. After 5 min and 24 h of contact, cell viability was assessed using the MTT assay. Results: Given these results, using 5 min of exposure time to the extracts, in ascending order of cell viability reduction follows green tea, with increased cell viability, pepper tree and artichoke. In the MTT assay of the extracts using exposure time of 24 h, it was observed that artichoke extract showed the greatest toxicity, followed by green tea and pepper tree extracts. Statistical analysis was performed by ANOVA and Tukey's test, with a significance level of 5%. Conclusions: Among the extracts, green tea with 12.5mg/mL had interesting results for 5 min and 24 h, since this was the highest concentration and it wasn't cytotoxic to the macrophages, and artichoke was the most cytotoxic to the macrophages in both times (5 min and 24 h).
Keywords: Green tea; artichoke; pepper tree; cytotoxic activity; macrophages